Environmental Education Program in the Balsa river basin, Costa Rica (Biocenosis, 2012)
This article presents the experience developed during the period 2011 - 2012 in schools in the areas of San Ramon andCiudad Quesada from five communities in the area of influence of Balsa Hydroelectric Project, built by the National Power and Light Company as part of Corporate Social Responsibility. Among the product highlights generated the creation of Green Clubs and Environmental Committees in each community. Each group develops, in conjunction with the project’s environmental educator, an annual action plan consisting of a monthly activity, organized in a fun way, so they are motivated to participate in pro-environmentalactions.
Keywords: Pro-environmental actions; Green Clubs; Environmental Committees; Rational use of water and electricity; Recovery of recyclable waste